Efficacy and safety of bifidobacterium quadruple viable tablets in the treatment of Helicobacter pylori-infected peptic ulcer or gastritis patients: a systematic review and meta-analysis - Xueliang Jiang; Chunjin Xu; Bo Liu; Ping Chen; Qinchang Xu; Lu Zhang (BMC Infectious Diseases, 2023)
Abstract Background To better understand the efficacy and safety of Bifidobacterium quadruple viable tablets in the treatment of helicobacter pylori (H. pylori)-infected peptic ulcer or gastritis patients. Methods A systematic review of the studies published to June 2022 was performed in English database PubMed, Embase, Chinese database CNKI, Wanfang. There were 17 studies were included in this systematic review and meta-analysis. The outcomes measured included H. pylori eradication rate, changes in clinical symptoms of epigastric pain scores, and the incidence of adverse reactions. Results The results of the fixed effect model showed that the eradication rate of H. pylori in the combination of Bifidobacterium quadruple viable bacteria tablets combined with bismuth-containing conventional quadruple therapy was greater than that of bismuth-containing conventional quadruple therapy, and the difference was statistically significant (OR = 3.73, 95%CI (2.79,5.00), Z = 2.78, P < 0.001; I2 = 0.0%, P > 0.999). The results of random effects model showed that the epigastric pain score of Bifidobacterium quadruple viable bacteria tablets combined with bismuth-containing conventional quadruple therapy was lower than that of bismuth-containing conventional quadruple therapy, and the difference was statistically significant (WMD=-0.70, 95%CI (-1.06,-0.34), Z = 3.82, P < 0.001; I2 = 96.7%, P < 0.001). The results of random effects model showed that the acid reflux score of Bifidobacterium quadruple viable bacteria tablets combined with bismuth-containing conventional quadruple therapy was lower than that of bismuth-containing conventional quadruple therapy, and the difference was statistically significant (WMD=-0.98, 95%CI (-1.70,-0.26), Z = 2.66, P < 0.001; I2 = 99.7%, P < 0.001). Conclusions The eradication rate of H. pylori by Bifidobacterium quadruple viable bacteria tablets combined with bismuth-containing quadruple therapy is better than that of bismuth-containing quadruple therapy. The improvement of clinical symptoms of patients is better than that of bismuth-containing quadruple therapy, and the incidence of adverse reactions is lower than that of bismuth-containing quadruple therapy. Bifidobacterium quadruple viable bacteria tablet combined with bismuth-containing quadruple therapy was effective and safe. It provides a new way to treat patients with H. pylori.